Continuous detection of extracellular ATP on living cells by using atomic force microscopy - Schneider, Stefan W. (The National Academy of Sciences, 1999)
Atomic force microscopy is a powerful technique used to investigate the surface of living cells under physiological conditions. The resolution of the instrument is mainly limited by the softness of living cells and the interactions with the scanning tip (cantilever). Atomic force microscopy, in combination with myosin-functionalized cantilevers, was used in the detection of ATP concentrations in solution and on living cells. Functionally active tips were used to scan the surface of cells in culture and to show that the CFTR+ cell line (S9) had a basal surface ATP concentration that could be detected with atomic force microscopy (n = 10). ATP-dependent signals were not detectable in cells scanned with noncoated or heat-inactivated enzyme-coated tips (n = 9). Enzymatically active tips may serve as a model for future development of atomic force microscopy biosensors that can simultaneously detect topographical and biologically important compounds at the surface microenvironment of living cells.